Functional analysis of the first complete genome sequence of a multidrug resistant sequence type 2 Staphylococcus epidermidis. Issue 9 (20th September 2016) - Lee, Jean Y. H.; Monk, Ian R.; Pidot, Sacha J.; Singh, Siddarth; Chua, Kyra Y. L.; Seemann, Torsten; Stinear, Timothy P.; Howden, Benjamin P.
Abstract : Staphylococcus epidermidis is a significant opportunistic pathogen of humans. The ST2 lineage is frequently multidrug-resistant and accounts for most of the clinical disease worldwide. However, there are no publically available, closed ST2 genomes and pathogenesis studies have not focused on these strains. We report the complete genome and methylome of BPH0662, a multidrug-resistant, hospital-adapted, ST2 S. epidermidis, and describe the correlation between resistome and phenotype, as well as demonstrate its relationship to publically available, international ST2 isolates. Furthermore, we delineate the methylome determined by the two type I restriction modification systems present in BPH0662 through heterologous expression in Escherichia coli, allowing the assignment of each system to its corresponding target recognition motif. As the first, to our knowledge, complete ST2 S. epidermidis genome, BPH0662 provides a valuable reference for future genomic studies of this clinically relevant lineage. Defining the methylome and the construction of these E. coli hosts provides the foundation for the development of molecular tools to bypass restriction modification systems in this lineage that has hitherto proven intractable.